HUBUNGAN ANTARA PARITAS, USIA, DAN PENDIDIKAN IBU HAMIL TRIMESTER III DENGAN TINGKAT KECEMASAN DALAM MENGHADAPI PERSALINAN DI PUSKESMAS BANJAR I - Luh Desia Ridayanti; Asep Arifin Senjaya; Ni Komang Erny Astiti (Midwifery Department of Health Polytechnic, Ministry of Health, Denpasar, 2023)
In the delivery process there is also an increase in anxiety, with increasing anxiety will further increase the intensity of pain. The phenomenon of the relationship between anxiety and pain, and vice versa is a positive correlation. The more advanced the delivery process, the more anxious the pregnant woman feels and this anxiety causes more intense pain and vice versa. This study aims to analyze the relationship between parity, age, and education of third trimester pregnant women with anxiety in facing childbirth at the Banjar I Health Center. The type of research used was analytic observational with a cross sectional design. The sample used in this study was 48 respondents with a data collection tool in the form of a questionnaire. Data analysis techniques using univariate analysis and bivariate analysis. The results of data analysis using the Rank Spearmen test between anxiety level and parity (p : 0.001), age (p : 0.003), and education (p : 0.08) p value 0.05. The conclusion of the study is that there is a relationship between parity, age, and education of third trimester pregnant women with anxiety in facing childbirth at the Banjar I Health Center. Suggestions that can be given are for pregnant women, especially third trimester pregnant women, to be more active in seeking information about factors influencing anxiety levels in facing labor. So that they understand and understand more about anxiety in the face of childbirth.